Natural ventilation of animal sheds due to thermal buoyancy and wind - Kavolėlis, Bronius; Bleizgys, Rolandas; Čėsna, Jonas (Journal of Environmental Engineering and Landscape Management, 2008)
In designing a natural ventilation system for animal sheds it is necessary to assess the ventilation induced by thermal buoyancy and wind forces during different seasons and under different animal housing conditions. By applying analytical and experimental investigation a methodology was prepared to establish ventilation intensity caused by thermal buoyancy and wind and data were achieved on thermal buoyancy and wind values and their relationship. The innovation of the methodology can be described by the fact that a simple equation was formed to calculate the air speed in inlet and outlet openings, a mathematical expression of thermal buoyancy and wind ratio was achieved and the required inlet opening area to let in fresh air compared with the outlet opening area to let out polluted air was substantiated to ensure that all polluted air is removed through a rooftop open in winter. It was calculated that the average air speed in the rooftop outlet opening of a typical cold‐type cowshed is 1.3 m/s (when there is no wind, this speed decreases to 0.3 m/s), thermal buoyancy and wind ratio is 0.27 and in order to have all polluted air removed through the rooftop open in winter the inlet opening area in the walls must not exceed 40% of the rooftop opening area. The accuracy of the prepared methodology was tested under natural conditions of barn operation when the distance between air inlet openings and outlet openings was 6.5 m. During the investigation indoor and outdoor temperatures, air speed in the outlet and wind speed were measured. During the experiments the difference of indoor and outdoor temperatures varied from –2 to +16°C and air speed in the outlet – from 1.2 to 1.9 m/s. The analytical results reflect the mean values of experimental data under natural conditions of operation rather accurately. The difference between the experimental and calculated air speed values in the outlet opening was insignificant and was within 0–8% range.Natūralus tvarto vėdinimas veikiant gravitacinei ir vėjo traukaiSantrauka. Projektuojant tvarto natūralaus vėdinimo sistemą, reikia įvertinti gravitacinės ir vėjo jėgos skirtingais metų laikais bei skirtingomis gyvulių laikymo sąlygomis sukeltą trauką. Taikant analizinius ir eksperimentinius tyrimus, sudaryta metodika gravitacinės ir vėjo traukos sukeltam vėdinimo intensyvumui nustatyti, gauti duomenys apie gravitacinės ir vėjo traukos reikšmes bei jų santykį. Metodika yra nauja. Sudaryta paprasta lygtis oro greičiui įėjimo ir šalinimo angose skaičiuoti, gauta gravitacinės ir vėjo traukos santykio matematinė išraiška, pagrįstas angų plotas, reikalingas šviežiam orui į patalpą įeiti. Šis plotas lyginamas su angų užterštam orui šalinti plotu, nes visas užterštas oras žiemą turi būti šalinamas per kraigo plyšį. Apskaičiuota, kad tipiškoje neapšiltintoje karvidėje vidutinis oro judėjimo greitis kraigo plyšyje – 1,3 m/s (kai vėjo nėra šis greitis sumažėja iki 0,3 m/s), gravitacinės ir vėjo traukos santykis – 0,27. Tam, kad žiemą visas šalinamas oras išeitų per kraigo plyšį, angų orui įeiti sienose plotas turi neviršyti 40 % kraigo plyšio ploto. Sudarytos metodikos tikslumas patikrintas tvarto natūralios eksploatacijos sąlygomis, kai atstumas tarp oro įėjimo angų ir šachtos viršaus – 6,5 m. Tiriant matuota patalpos ir lauko oro temperatūra, oro greitis šachtoje. Tyrimų metu patalpos ir lauko oro temperatūrų skirtumas kito nuo –2 °C iki +16 °C, o oro judėjimo greitis šachtoje – nuo 1,2 m/s iki 1,9 m/s. Analiziniai rezultatai pakankamai tiksliai atspindi eksperimentinių duomenų vidurkį tvarto natūralios eksploatacijos sąlygomis. Eksperimentinių ir apskaičiuotų oro judėjimo šalinimo angoje greičių reikšmių skirtumas buvo nežymus ir svyravo nuo 0 % iki 8 %.Reikšminiai žodžiai: natūralus vėdinimas, gravitacija, vėjas, santykis, parametrai.Воздухообмен животноводческого помещения под действием тепловых избытков и ветраРезюме. При проектировании системы воздухообмена здания необходимо учитывать воздухообмен, происходящий под действием тепловых избытков и ветра в разные сезоны года и при разных условиях содержания животных. В результате аналитических и зкспериментальных исследований разработана методика для расчета параметров системы воздухообмена животноводческого помещения, которая обеспечивает стабильную тягу. В методике приведены простые формулы для расчета скорости воздуха в приточных и вытяжных проемах, для определения рационального соотношения площади приточных и вытяжных проемов, для отдельного учета действия тепловых избытков и ветра на производительность системы воздухообмена. Согласно расчетам в типичном неутепленном коровнике шириной 21 м средняя скорость вытяжного воздуха в коньковой щели составляет 1,3 м/с (при отсутствии ветра – 0,3 м/с), соотношение гравитационной и ветровой тяги – 0,27. Для обеспечения стабильной тяги в холодный период года площадь приточных стеновых проемов должна составлять не более 40% площади конькового проема. Точность методики проверена в условиях натуральной эксплуатации животноводческого помещения, в котором расстояние между центрами приточных и вытяжных проемов равно 6,5 м. Во время исследований измерялась наружная и внутренняя температура воздуха, скорость движения воздуха в вытяжном проеме и скорость ветра. Температурный перепад между внутренним и наружным воздухом изменялся от –2 °С до +16 °С, а скорость движения воздуха в вытяжном проеме была 1,2–1,9 м/с. Разница между результатами расчета и экспериментальными данными не превышала 8%. Поэтому можно утверждать, что точность разработанной методики достаточна.Ключевые слова: естественный воздухообмен, тепловые избытки, ветер, соотношение, параметры.First Published Online: 14 Oct 2010